2009
DOI: 10.1080/16506070902966918
|View full text |Cite
|
Sign up to set email alerts
|

Distress and Avoidance in Generalized Anxiety Disorder: Exploring the Relationships with Intolerance of Uncertainty and Worry

Abstract: Theory and research suggest treatments targeting experiential avoidance may enhance outcomes for patients with GAD (Roemer & Orsillo, 2002; 2007). Preliminary findings demonstrate that distress about emotions and avoidance of internal experiences share unique variance with GAD above and beyond chronic reports of worry (Roemer, Salters, Raffa, & Orsillo, 2005). The purpose of the present study was to extend previous findings to explore the role of experiential avoidance and distress about emotions in a treatmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
59
0
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 103 publications
(70 citation statements)
references
References 35 publications
(50 reference statements)
8
59
0
3
Order By: Relevance
“…It is associated with high levels of worry and catastrophic predictions plus counter-productive coping behaviour. [48] Patients susceptible to motor fluctuations and who find the experience distressing report 'testing' their motor function or 'scanning' for signs of an impending off-period that would require a dose of medication. Such attentional focus on, and attempt to control, an often unpredictable event typically serves to maintain state anxiety rather than reduce it.…”
Section: Discussionmentioning
confidence: 99%
“…It is associated with high levels of worry and catastrophic predictions plus counter-productive coping behaviour. [48] Patients susceptible to motor fluctuations and who find the experience distressing report 'testing' their motor function or 'scanning' for signs of an impending off-period that would require a dose of medication. Such attentional focus on, and attempt to control, an often unpredictable event typically serves to maintain state anxiety rather than reduce it.…”
Section: Discussionmentioning
confidence: 99%
“…Research has shown that intolerance of uncertainty and worry are highly related (Dugas & Koerner, 2005). Numerous researchers have discussed intolerance of uncertainty and its relationship to worry (Lee et al, 2010;Nuevo et al, 2009;Dugas & Koerner, 2005;Dugas et al, 1997). However, most of these studies had young adults as respondents (Lee et al, 2010;Dugas & Koerner, 2005;Rosen & Knauper, 2009) compared to the few investigations which involved the elderly group (Nuevo et al, 2009;Dugas et al,1997).…”
mentioning
confidence: 93%
“…In fact, Borkovec (Borkovec & Sharpless, 2004) proposes that these "reactions to reactions" should be the target for change in treatment. Research supports these observations: clients with GAD report fear of their own bodily sensations (i.e., anxiety sensitivity; Olatunji & Wolitzky-Taylor, 2009), negative reactions to a range of emotions (Lee, Orsillo, Roemer, & Allen, 2010;Mennin, Holaway, Fresco, Moore, & Heimberg, 2007), and worry about their own worry (Wells, 2005). The tendency to narrow attentional focus toward threat (Cisler & Koster, 2010) likely further intensifies these reactions, so they spiral to become even more negative, distressing, and all-encompassing.…”
Section: Critical Reactive Fused Relationship With Internal Experiementioning
confidence: 67%
“…This experientially avoidant function of worry appears to reduce distressing internal experiences, in the short term, although it likely prolongs them over time by interfering with emotional processing (recovery) as well as preventing recognition of the adaptive information provided by emotional states . If experiential avoidance is a central problem in GAD (Lee et al, 2010), then experiential acceptance, which mindfulness practice promotes, may be the solution.…”
Section: Rigid Experiential Avoidancementioning
confidence: 99%